RANCANG BANGUN APLIKASI KAMUS BAHASA SUMBAWA BERBASIS ANDROID - Nora Dery Sofya; Shinta Esabella; Rodianto Rodianto (Universitas Bumigora, 2017)
The purpose of this writing is to design and to develop an application that is able to present data in Sumbawa Language (Basa Samawa) Dictionary which is still in book outline into digital form. Spiral method is used in this research for software development process and its data collection method applies literature study with data source from